The impact of using smartphones in two different sitting postures on muscle tension and fatigue in Thai young adults: a pilot study - Pongjan Yoopat; Sureemas Kladkunsaeng; Kamolchanok Chotisutra; Kamiel Vanwonterghem (Journal of Current Science and Technology, 2019)
This study aimed to assess the impact of smartphone uses in different sitting postures on the muscle activity of the back, neck, and upper extremities of Thai young adults. Seventeen male and female university students were randomly asked to perform text messaging communication via their smartphones using a social media program in two different sitting postures; 15 minutes in straight back posture (sb) followed by 15 minutes in not straight back posture (nb). The speed of data input was 40 words per minute. The EMG intensity and the change of spectral frequency were analyzed. The muscle of the back, neck, and upper extremities of eight muscles in both left and right sides were M.neck extensor, LNEX, RNEX; M.trapezius, LTRP, RTRP; M.wrist flexor, LWFL, RWFL; and M.wrist extensor, LWEX, RWEX. The results showed that the not straight back sitting posture with the text messaging via the smartphone reflected a fatigue level in M. left neck extensor (p<0.05). There was a decrease in the EMG intensity while performing a Maximum Voluntary Contraction of the M. right neck extensors and M. left trapezius after the 30-minute use of the smartphone device (p<0.05). These results indicate that the 30-minute use of smartphones with the data input of 40 words per minute without paying attention to the sitting posture increases muscle tension and muscle fatigue in Thai young adults.∆MPF